The Role of Higher Education in Achieving Sustainable Development Goals: A Comparative Study between Jordan and Morocco with Potential Applications in Libya. - Zarouqa, Ebtisam Belgasem Mohamed Zarouqa; Thlej, Ebtisam Thlej Faraj Thlej (Sharwes Scientific Journal, 2025)
This study aims to analyze the role of higher education in achieving the Sustainable Development Goals (SDGs) through a comparative analysis of the Jordanian and Moroccan experiences, while exploring the potential benefits of these experiences within the Libyan context. The study adopted a descriptive-analytical approach, relying on both primary and secondary sources that were carefully collected and analyzed. The analysis focused on university policies and institutional initiatives related to sustainable development in both countries. The results revealed significant differences in the degree of integration between higher education institutions and the SDGs. Moroccan universities were found to be more proactive in embedding sustainability concepts into their curricula and strategic plans compared to their Jordanian counterparts. The study concluded that the Libyan higher education system could benefit from both experiences by developing flexible university policies, strengthening partnerships with various societal sectors, and adopting a comprehensive approach to sustainability. The study recommends incorporating SDGs into the vision and mission of Libyan universities and restructuring academic programs to align with both local and global development needs.